The Minister of the Treasury’s survey of the Italian economic situation in 1952 - LUTZ, V.C. (PSL Quarterly Review, 2014)
The article summarises the principal statistics relating to national income, consumption and investment in Italy over the last three years as given in Signor Pella’s latest (fourth) Annual Report supplemented by that for the previous year. It also reproduces from the same source the balance of payments statistics for the last two years as they result from the receipts and payments of foreign exchange registered by the Italian Foreign Exchange Office. Two aspects of Italian economic developments in 1952 stand out from the present Report. The first is the decline in the rate of expansion of production and investment as compared with previous years. The second is the serious deterioration in Italy’s balance of payments position, reflected especially in the reversal of the movement of her balances with the European Payments Union. JEL: E01, E20, F31, F32, O52